ANALISIS PENYEBARAN CAHAYA PADA LABORATORIUM DI GEDUNG TEKNIK ELEKTRO FAKULTAS TEKNIK UNIVERSITAS PAPUA: Analysis Of Light Distribution In The Laboratory In The Electrical Engineering Building, Faculty Of Engineering, University Of Papua - Hasrul Bugis; Jamius B. Stepanus; Foury Y.S Paisey (JISTECH: Journal of Information Science and Technology, 2023)
The laboratory room in the Department of Electrical Engineering, Faculty of Engineering, University of Papua is a room with the main activities of reading, writing and practicum. The Electrical Engineering laboratory room has two practicum rooms, namely electrical laboratory rooms 1 and 2 with a room area of 79,695 m^2. Electrical laboratory rooms 1 and 2 have artificial lighting, the number of lights installed in the room is 13 light points, consisting of 9 types of TL lamps with a lamp power capacity of 2x36 watts/72 lumens and 4 types of Phileps Essential lamps 1x8 watts/54 lumens In this research, an analysis was carried out on the distribution of light in each laboratory room in Electrical Engineering, Faculty of Engineering, University of Papua, because it was suspected that there was a lack of lighting intensity in laboratory rooms 1 and 2. The method used in this research was the direct observation method, defined as observing, measuring, and systematic recording of symptoms that appear on the research object. Measuring the intensity of lighting using a luxmeter obtained measurement values of 255,6 lux (electrical laboratory 1) and 266,82 lux (electrical laboratory 2). The calculation results of the lighting intensity in the Electrical Engineering Laboratory 1 room were 399.32 lux, and in the Electrical Laboratory 2 room it was 257,66 lux. When compared, the standard value is still taken according to the requirements of the Indonesian National Standard (SNI 03-6575-2001), namely a minimum of 500 lux.